The Tixall circle and the musical life of St Monica’s, Louvain - Stevenson, J (Cambridge University Press, 2017)
This article explores the possibility that poems preserved in the recusant coterie collection, Tixall Poetry may include verses written both by and for the Augustinian canonesses of St Monica’s, Louvain, and provide evidence for the cultural life of the convent. It then turns to a consideration of evidence for the cultivation of music, and argues for the practical importance of music to the lives of the canonesses. It explores the intense significance which the canonesses attached to the clothing ceremony, and suggests that one of the Tixall poems, ‘The Royal Nun’, an adaptation of two lyrics from Nathanael Lee’s play Theodosius (1680), perhaps by Herbert Aston, might have been used as the libretto for the music which, when possible, covered the hiatus in the clothing ceremony when the nun took off her bridal garments and assumed her habit.